Rollercoaster Ride Called Ph.D. - Diyana, Kamarudin (Penerbit UMP, 2020)
Before reading about my PhD journey, let me introduce you to my background a little bit. My parents are both scholars and because of this, I have spent most of my life moving from one place to another.